Resilience as the predictor of quality of life in the infertile couples as the most neglected and silent minorities. (4th May 2022) - Vatanparast, Mahboubeh; Yasini Ardekani, Seyed Mojtaba; Anvari, Morteza; Kalantari, Athareh; Yaghmaie, Farideh; Royani, Zahra
ABSTRACT: Background: It has been demonstrated that infertility can affect quality of life (QoL) in infertile couples. Resilience is considered a protective factor against the distress caused by infertility and the quality of life status. There is a new definition for Fertility Quality of Life that evaluates particularly the impact of infertility on various aspects of life. Material and methods: In this couple-based study, the main objective was investigating the quality of life based on the gender and resilience of infertile couples. Measurement tools were three questionnaires including a demographic one, a quality of life of infertile couples questionnaire and the Connor–Davidson Resilience Scale. Data analysis was done through paired t -test and linear multiple regressions test. Results: Overall the difference of mean score for QoL is statistically significant ( P > 0.001) between men and women (69.48% vs 58.87%), which means that QoL status was positive in men and neutral in women. In addition, the mean score of male resilience was more than female resilience ( P = 0.009). The results showed there was a significant and positive correlation between the QoL status and resilience score ( P = 0.008, r = 0.13) ( P < 0.1), and resilience (β = 0.04 and P = 0.04) had a significant protective effect on the quality of life. Conclusion: Low resilience status in infertile couples is better to be considered as a risk factor compromising the quality of life and infertility consolers should keep in mind this issue and provide a comprehensive and holistic approach for a better outcome of infertility treatment. Abbreviations: QoLICQ: Quality of Life in Infertile Couple Questionnaire; CD-RISC: Connor–Davidson Resilience Scale; IVF: in vitro fertilisation; ART: assisted reproductive technique; PTSD: posttraumatic stress disorder; IUI: intrauterine insemination; ICSI: intracytoplasmic sperm injection.